Foreign direct investment in India. - Mahatma, S. (2008)
India's attractiveness for Foreign Direct Investment (FDI) and the amount of FDI invested are increasing continuously in the recent times. The Indian government understood the need for FDI and has liberalized its policies to attract more FDI. The state governments of various states are also competing with one another to attract more FDI by providing more facilities, incentives, etc. With the ongoing liberalization process some industries are found to be potential industries for future FDI. The pattern of FDI at the national level based on the type of FDI and the destinated industries, the state level determinants of FDI based on their locational advantages are studied using the annual approved FDI data. The potential industries for future FDI, the expected policy changes in the near future and their possible impact on FDI have also been studied.